Assessment of nutrient removal and microbial population dynamics in a non-aerated vertical baffled flow constructed wetland for contaminated water treatment with composite biochar addition. (15th September 2019) - Meng, Fanchen; Feng, Lijuan; Yin, Haojie; Chen, Kongqing; Hu, Guanghui; Yang, Guangfeng; Zhou, Jiaheng
Abstract: A novel composite biochar (NCB) was produced from the pyrolysis of co-fermentation products of sewage sludge, food wastes and rice straw, and exhibited higher nitrogen and phosphorus adsorption capacity due to the larger surface area (14.7 m 2  g −1 ) and higher Ca content (51753.7 mg kg −1 ) than single rice straw biochar. The addition of NCB was then investigated in a non-aerated vertical baffled flow constructed wetland (VBFCW) for contaminated water treatment. The VBFCW with NCB addition significantly improved CODMn, NH4 + -N, TN and TP removal efficiencies of 83.3 ± 5.3%, 95.9 ± 3.4%, 28.0 ± 4.0% and 59.5 ± 11.8%, respectively, at a hydraulic retention time (HRT) of 3 d. In addition, the TN and TP removal rates at a decreased HRT of 2 d were much higher than those at an HRT of 3 d without NCB addition. The presence of NCB in the VBFCW system enhanced nutrient adsorption and improved the enrichment of bacteria for organic and nitrogen removal mainly including the genera Bacillus and Lactococcus . Highlights: Novel composite biochar (NCB), pyrolysis from fermented sludge-food wastes-rice straw. NCB had good adsorption for N and P due to large surface and high Ca content. NCB addition improved the removal of organics, N and P in CWs. NCB addition favored to achieve efficient nutrients removal in CWs at short HRT. NCB improved enrichment of nitrogen and organics removal related bacteria in media.